Secondary antibody deficiencies: what’s around the corner? - Lagnese, Gianluca; Messuri, Carla; Poto, Remo; Varricchi, Gilda; Spadaro, Giuseppe (Frontiers in Immunology, 2025)
Secondary antibody deficiencies (SADs) are characterized by impaired humoral immunity, which can cause recurrent and severe infections. Several factors may contribute to SAD development, making it difficult to establish a clear etiological classification. This heterogeneity also leads to clinical variability, further complicating patient management and treatment strategies. Various diagnostic and therapeutic algorithms are often adapted from those used in primary antibody deficiencies, potentially resulting in under- or over-treatment. Key points include the decision to initiate Immunoglobulin Replacement Therapy (IgRT) and the duration of the treatment. Given the increasing prevalence of SADs and the limited availability of immunoglobulin products, it is important to clarify when IgRT should be started. In this review, we summarize and update the different etiologies of SADs and propose a diagnostic algorithm applicable regardless of the underlying cause. We also examine the possible treatment options and diagnostic tools that can assist in making the correct therapeutic choice.